Numerical simulation of surface diffusion motion and its application in MEMS fabrication. (August 2019) - Zhang, Yujie; Zeng, Fan; Wong, Man; Xiang, Junping; Ye, Wenjing
Abstract: Surface diffusion motion has been proposed as a new technique, called Silicon Migration Technology (SiMiT) for the fabrication of Micro-Electro-Mechanical System (MEMS) devices. Using this new technology, the integration of MEMS-CMOS can be achieved without the "sacrificial-structural" layers and "release-etch" procedure, which are necessary in traditional approaches. However, numerical simulation of surface diffusion process is still a challenging task due to the stiffness nature and the topological changes during the process. In this paper, we adopted a high-order explicit level-set method based on the total variation diminishing Runge-Kutta (TVD-RK) method, a high-order scheme for distance computation. An efficient smoothing scheme is proposed to increase the numerical stability and an adaptive time marching scheme is developed to accelerate the simulation. Experimental investigation of shape transformation of silicon trenches is carried out to verify the accuracy of the numerical scheme. Results show that numerical simulation results match quite well with experimental ones, which suggests the accuracy and reliability of the numerical simulation in the application of MEMS design.